Penggunaan Abu Batang Padi sebagai Bahan Tambah pada Campuran AC-BASE Menggunakan Batu Sungai Parekaju Kabupaten Luwu - Maylki Datu Bara; Robert Mangontan; Alpius (Paulus Civil Engineering Journal, 2022)
The rest of the rice farm such as rice stalks are simply thrown away and not utilized optimally while the availability is very abundant during the harvest season. Based on a study source, it is known that the main component of the cell wall in rice stems contains high silica, which is 70.8% so that this large enough content makes rice stems a potential source of silica to be used in the laston AC-BASE mixture to increase compressive power on asphalt. This research was conducted to find out how the effect of adding rice stem ash to the laston mixture by referring to the provisions of the 2018 Bina Marga. From testing using 5 variations in levels, an increase in flow values, a decrease in VMA and VIM, a significant increase in stability and VFB were obtained. All test results in this study are in accordance with the provisions of Bina Marga.